Intervensi Senam untuk Meningkatkan Kualitas Tidur pada Lansia dengan Gangguan Tidur - Theresia Eriyani; Iwan Shalahuddin; Sandra Pebrianti; Indra Maulana; Devi Nurrahmawati (Malahayati Nursing Journal, 2023)
ABSTRACT The elderly will experience physical, psychosocial and spiritual changes. One such change is a change in sleep quality. According to the National Sleep Foundation (NSF) about 67% of the 1,508 elderly in America aged 65 years and over reported having sleep disturbances and as many as 7.3% of the elderly complained of impaired initiation and maintaining sleep or insomnia. Sleep disturbances can cause disturbances in activities so that productivity decreases which often interfere with their activities. This study aims to determine the effect of gymnastics intervention in the elderly with insomnia on improving the quality of sleep of the elderly. This study used a scoping review method approach. The databases used in the search for related literature are Pubmed and ScienceDirect. Article searches are conducted using English keywords namely "Elderly with Insomnia" AND " Gymnastics" AND "Sleep Quality.  To make it easier to get suitable literature, inclusion criteria in article searches include the year of publication of articles from 2016-2020, articles in full text and in English. The selected articles are research-type articles with quasi-experimental research designs, clinical trials and RCTs (Randomized Controlled Trial, and articles with a total sample of at least 30 people. After searching through several sources using predetermined keywords, article sorting was carried out with the results of 4 articles with a temporary conclusion that it was found that there are several types of gymnastics that can be given to improve the sleep quality of the elderly who experience sleep disorders, including yoga therapy exercises, pilates, tai chi and baduanjin. Of the four gymnastics, there was a significant improvement in the sleep quality of the elderly who experienced sleep disorders. Based on the results of the literature review that we have carried out, it shows that sleep quality disorders in the elderly can be given interventions in the form of gymnastics exercises. Based on the results of the literature review that we have conducted, there are implications that can be used for improvement in nursing, especially in interventions. That by doing gymnastics can have an influence to overcome sleep disorders in elderly patients Keywords : Gymnastics, Sleep, Elderly, Influences, Sleep Disorders   ABSTRAK Lansia akan mengalami perubahan-perubahan fisik, psikososial dan spiritual. Salah satu perubahan tersebut adalah perubahan kualitas tidur. Menurut National Sleep Foundation (NSF) sekitar 67 % dari 1.508 lansia di Amerika usia 65 tahun keatas melaporkan mengalami gangguan tidur dan sebanyak 7,3 % lansia mengeluhkan gangguan memulai dan mempertahankan tidur atau insomnia. Gangguan tidur dapat menyebabkan gangguan pada aktivitas sehingga turunnya produktivitas yang sering kali mengganggu kegiatannya. Penelitian ini bertujuan untuk mengetahui Pengaruh intervensi senam pada lansia dengan insomnia terhadap peningkatan kualitas tidur lansia.  Penelitian ini menggunakan pendekatan metode scoping review. Database yang digunakan dalam pencarian literatur terkait yaitu Pubmed dan ScienceDirect. Pencarian artikel dilakukan dengan menggunakan kata kunci berbahasa Inggris yaitu “Elderly with Insomnia” AND “ Gymnastics” AND “Sleep Quality.  Untuk memudahkan mendapatkan literatur yang sesuai digunakan Kriteria inklusi dalam pencarian artikel diantaranya tahun terbit artikel dari  2016-2020, artikel berbentuk full text dan berbahasa inggris. Artikel yang dipilih merupakan artikel berjenis penelitian dengan desain penelitian quasi eksperimen, clinical trial dan RCT (Randomized Controlled Trial, dan artikel dengan total sampel minimal 30 orang. Setelah melakukan pencarian melalui beberapa sumber dengan menggunakan kata kunci yang telah ditetapkan, dilakukan penyortiran artikel dengan hasil 4 artikel dengan Kesimpulan sementara didapatkan bahwa terdapat beberapa jenis senam yang dapat diberikan untuk meningkatkan kualitas tidur lansia yang mengalami gangguan tidur, diantaranya latihan terapi yoga, pilates, tai chi dan baduanjin. Dari keempat senam tersebut menunjukkan peningkatan yang signifikan terhadap kualitas tidur lansia yang mengalami gangguan tidur. Berdasarkan hasil literature review yang telah kami lakukan menunjukkan bahwa gangguan kualitas tidur pada lansia dapat diberikan intervensi berupak latihan senam. Berdasarkan hasil literatur review yang telah kami lakukan, terdapat implikasi yang dapat digunakan untuk peningkatan dalam keperawatan khususnya dalam intervensi. Bahwa dengan melakukan senam dapat memberikan pengaruh untuk mengatasi gangguan tidur pada pasien lansia. Kata Kunci: Senam, Tidur, Lansia, Pengaruh, Gangguan Tidur